Donald Duck around the world in 8 days - Chendi, Carlo; Carpi, Giovan Battista ([London] : Paperview Europe)
"In this parody of Around the world in eighty days, it is Uncle Scrooge rather than Phileas Fogg who makes a bet with other members of his club. In this case it is the Billionaires Club, and he bets he can go around the world in eight days--without spending a penny!"--Cover.
Keywords: Duck, Donald (Fictitious character) -- Comics books, strips, etc